2020
DOI: 10.1016/j.jebo.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Micro-level transmission of monetary policy shocks: The trading book channel

Abstract: We open the black box of the monetary policy transmission mechanism with a granular model that considers the balance-sheet composition and network relationships of each economic agent. Though there are several well-documented channels through which monetary policy operates, we focus on the overlooked trading book channel, which arises because of adjustments in the accounting value of trading book exposures on banks’ balance sheets that have to be marked to market when interest rates change. Variations in banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…There is substantial research in the literature employing complex networks to investigate subjects within the field of economics and finance. These studies encompass diverse topics such as stock returns during the Global Financial Crisis [12], volatility of stock prices [20], the interplay between COVID-19 and the stock market [21], the prediction of financial crises through machine learning techniques [22], the effects of monetary policy shocks [23], investment strategies in the global context [24], the connectedness of the global bank network [25], trust within banking networks [26], financial networks and banking efficiency [27], the relationship between firm network structure and innovation [28], the impact of migrant networks on FDI [29], and the estimation of vulnerability and the diffusion of impact [30].…”
Section: Related Workmentioning
confidence: 99%
“…There is substantial research in the literature employing complex networks to investigate subjects within the field of economics and finance. These studies encompass diverse topics such as stock returns during the Global Financial Crisis [12], volatility of stock prices [20], the interplay between COVID-19 and the stock market [21], the prediction of financial crises through machine learning techniques [22], the effects of monetary policy shocks [23], investment strategies in the global context [24], the connectedness of the global bank network [25], trust within banking networks [26], financial networks and banking efficiency [27], the relationship between firm network structure and innovation [28], the impact of migrant networks on FDI [29], and the estimation of vulnerability and the diffusion of impact [30].…”
Section: Related Workmentioning
confidence: 99%
“…In Georg (2013) and Bluhm et al (2014), for instance, the central bank provides liquidity in the interbank market. Meanwhile, Silva et al (2020) estimate both direct and indirect impacts of monetary policy shocks (as measured by changes in the policy interest rate) on the economy by applying a multi-layer network model to a unique Brazilian data set.…”
Section: An Important Question Raised By Many Studies Is What Topolog...mentioning
confidence: 99%
“…In a different framework, using agent-based modeling, Riccetti et al [20] found a significant role for a financial accelerator that was founded on three dimensions: a leverage one, a stock market one, and a network one. We can also mention the study by Silva et al [21], who consider a granular approach that takes into consideration the network relationships between agents, along with the balance sheets compositions. The inclusion of network data allowed them to study contagion effects as well.…”
Section: Introductionmentioning
confidence: 99%